The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1002/pro.740
|View full text |Cite
|
Sign up to set email alerts
|

Insights into the structural stability of Bax from molecular dynamics simulations at high temperatures

Abstract: Bax is a member of the Bcl-2 protein family that participates in mitochondrion-mediated apoptosis. In the early stages of the apoptotic pathway, this protein migrates from the cytosol to the outer mitochondrial membrane, where it is inserted and usually oligomerizes, making cytochrome c-compatible pores. Although several cellular and structural studies have been reported, a description of the stability of Bax at the molecular level remains elusive. This article reports molecular dynamics simulations of monomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 75 publications
(90 reference statements)
6
12
0
Order By: Relevance
“…), closer analyses show substantial differences in the compactness of the protein. The radius of gyration (Rg) shows that the WT protein remains compact, with values mostly below 1.8 nm in full agreement with previously reported results . Meanwhile, changes in the Rg are observed for the structure of the mutant variants of Bax at 500 K (Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…), closer analyses show substantial differences in the compactness of the protein. The radius of gyration (Rg) shows that the WT protein remains compact, with values mostly below 1.8 nm in full agreement with previously reported results . Meanwhile, changes in the Rg are observed for the structure of the mutant variants of Bax at 500 K (Fig.…”
Section: Resultssupporting
confidence: 90%
“…Root mean square fluctuation (RMSF) values are consistent with previously reported data, with BH2 as the BH domain with the largest mobility (Fig. S3) . The final structures from the MD simulations are shown in Fig.…”
Section: Resultssupporting
confidence: 90%
“…According to the level of thermal stress, diverse conformations of Bcl-2 are obtained. In particular, simulations at temperatures less than or equal to 500 K provide possible structures related to active or inactive forms, whereas at temperatures above 500 K, an unfolding process could be proposed (Chen, Li, & Ma, 2009;Rosas-Trigueros, Correa-Basurto, Benítez-Cardoza, & Zamorano-Carrillo, 2011). Concerning functionality, snapshots show that the conformational movements led to the interaction between the Bcl-2 FLD and the protein core (Figure 4), which might be related to a regulation of Bcl-2 phosphorylation, caspase cleavage, and the interaction of Bcl-2 with pro-apoptotic proteins (Blagosklonny, 2001;Deng et al, 2006;Haldar et al, 1998;Huang et al, 1998;Kazi et al, 2011;Kirsch et al, 1999;Lin et al, 2004;Reed et al, 1996;Ruvolo et al, 2001;Srivastava et al, 1999).…”
Section: Bcl-2-δ22σ3 Rmsd Valuesmentioning
confidence: 99%
“…LEPRWT and LEPRR models were submitted to MD simulations during 1 ns and the last snapshot was stereochemically analyzed. To gain insight in the global behavior of the LEPR when the polymorphism Q223R is present, the Root Square Mean Deviation (RSMD) and the fluctuation of the alpha carbons were calculated (Bruschweiler, 2003;Rosas-Trigueros et al, 2011). Firstly, the RMSD showed that the equilibration was reached more rapidly in the WT (150 ps) model than in the mutant model (200 ps).…”
Section: Resultsmentioning
confidence: 99%
“…The system was constituted by the LEPR protein and water; afterwards we performed an energy minimization to obtain the initial coordinates for the phase of simulations of production. MD simulations were performed using a NVT ensemble at 300 K during 1 ns (Hess et al, 2008;Rosas-Trigueros et al, 2011).…”
Section: Methodsmentioning
confidence: 99%